Bagasse Ash Reinforced A356 Alloy Composite: Synthesis and Characterization. (2018) - Satish Kumar, T.; Shalini, S.; Kumar, K. Krishna; Thavamani, R.; Subramanian, R.
Abstract: Sugarcane bagasse has been attracting attention recently as a highly potential and versatile ingredient in composite materials due to its availability, low cost and biodegradability. In the present study, bagasse ash particles reinforced A356 alloy composites were produced by stir-casting method. 2, 4, 6, 8 and 10 wt% of bagasse ash particles were added to the base alloy for successful synthesis of composites. Density, microstructure and mechanical properties of the unreinforced alloy and the composites were studied. Density of the composites decreased with increase in wt% of bagasse ash particles. As-cast microstructure of the composites confirms the uniform distribution of bagasse ash particles. Significant improvement in the hardness, compressive strength, tensile strength and decrease in impact strength of the composites was observed with increase in wt% of bagasse particles. These results confirm that bagasse ash particles reinforced composites can give enhanced properties at lower densities.